UPAYA PENINGKATAN KINERJA PEDAGANG KAKI LIMA DI KOTA SURAKARTA MELALUI ORIENTASI KEWIRAUSAHAAN DAN KOMPETENSI KEWIRAHAAN - Hariyanti Hariyanti; Nuryati Nuryati (STIE AUB Surakarta, 2019)
This research is to analyze the effect of entrepreneurial orientation on performance through entrepreneurial competence at street vendors in the city of Surakarta. A sample of 99 street vendors. The analytical tool used is path analysis. The results of the study show that (1). Equation model 2 is the best model to explain performance through entrepreneurial orientation and entrepreneurial competence, (2) entrepreneurial orientation as measured by innovation, proactivity, risk-taking and entrepreneurial competence has a positive and significant effect on performance.the results of this study can be expected to contribute to police studies for the development to entrepreneurial orientation and entrepreneurial competence of street vendors, especially street vendors who sellin the of Surakarta.